2007
DOI: 10.1200/jco.2007.25.18_suppl.lba1008
|View full text |Cite
|
Sign up to set email alerts
|

BCIRG 007: First overall survival analysis of randomized phase III trial of trastuzumab plus docetaxel with or without carboplatin as first line therapy in HER2 amplified metastatic breast cancer (MBC)

Abstract: LBA1008 Background: Based on preclinical synergism between docetaxel (T), carboplatin (C) and trastuzumab (H), BCIRG conducted a phase III trial in HER2-positive MBC to evaluate efficacy and safety of H in combination with T or TC. Methods: 263 patients (pts) with HER2 FISH+ MBC were randomized to TH (H with T 100mg/m2) or TCH (H with T 75mg/m2 and C AUC=6). Chemotherapy was given every 3 weeks (q3w) for 8 cycles with weekly H at 2mg/kg (loading dose of 4 mg/kg) followed by H q3w at 6 mg/kg until progression.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Several trials are evaluating combinations of these drugs and other targeted therapies with chemotherapy in the first-line MBC setting. Phase III trial results are summarized in Table 2 [ 13 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ].…”
Section: Recurrent or Refractory Diseasementioning
confidence: 99%
“…Several trials are evaluating combinations of these drugs and other targeted therapies with chemotherapy in the first-line MBC setting. Phase III trial results are summarized in Table 2 [ 13 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ].…”
Section: Recurrent or Refractory Diseasementioning
confidence: 99%
“…Women (n ϭ 263) with HER-2-positive MBC were randomized to receive either docetaxel (100 mg/m 2 ) with trastuzumab, TH, or docetaxel (75 mg/m 2 ), carboplatin (AUC, 6 mg/ml per minute), and trastuzumab, TCH ( Fig. 1, Table 1) [59]. Approximately 72.5% of patients in both groups responded to treatment.…”
Section: Phase IIImentioning
confidence: 99%
“…Cardiotoxicity was negligible in both groups and there was no difference in cardiac events between the two regimens. Accordingly, the BCIRG 007 investigators concluded that both TH and TCH were equally effective therapies in women with HER-2-positive MBC [59].…”
Section: Phase IIImentioning
confidence: 99%
“…The addition of platinum salts to a taxane-trastuzumab combination was investigated in two large, phase III, randomized trials, with conflicting results [48,49]. Therefore, the role of a triplet combination is still a matter of study.…”
Section: Hormone Receptor-negative Her-2 ؉ Metastatic Breast Cancermentioning
confidence: 99%